Konsolidasi Masyarakat dengan Kesalehan Beragama, Pemberdayaan Ekonomi dan Pendidikan Pedesaan - Husrin Konadi (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2022)
Real work lectures (KKN) are a vehicle for the application and development of knowledge carried out outside the campus within certain time, work mechanisms, and requirements. Implemented by universities, is an effort to increase the content and weight of education for students and to get greater added value in higher education. With the implementation of this KKN is expected to develop social competence and personality competence of students. The purpose of this service is to strengthen community religious piety, develop community learning activity centers, help improve the economy of rural communities and strengthen rural institutions. The methods used in this service are the service learning method and the ABCD (Asset - Based Community Development) method. The results of KKN student service are being able to apply to the 4 programs that have been provided by the campus including 1). strengthening the religious piety of the community includes: TPA teaching/assistance, Ta'lim after dawn prayers with the al-Fajri musholla congregation, Ramadan Tarhib, Ramhadan tarhib activities, Ta'jil distribution, Fun in Ramadan, Bandar sub district competitions, Wirid mothers, Ramadhan Safari, Fundraising for al-Fajri Musholla. 2). The initiation of the establishment of a community learning center (PKBM) includes: motivational seminars and children's learning guidance. 3). Economic empowerment of rural communities includes: sewing courses and oyster mushroom cultivation. 4) strengthening of rural institutions includes: reading houses.